1996
DOI: 10.1073/pnas.93.1.316
|View full text |Cite
|
Sign up to set email alerts
|

Estrogens increase the expression of fibulin-1, an extracellular matrix protein secreted by human ovarian cancer cells.

Abstract: Ovarian cancers have a high ability to invade the peritoneal cavity and some are stimulated by estrogens. In an attempt to understand the mode of action of estrogens on these cancer cells and to develop new markers, we have characterized estrogen-regulated proteins. This study was aimed at identifying a protein secreted by ovarian cancer cells whose level was increased by estradiol [Galtier-Dereure,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
1
3

Year Published

1998
1998
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 25 publications
3
57
1
3
Order By: Relevance
“…Although coordinated expression of these two isoforms has been described , abnormal differential expression of the two isoforms in tumour tissues cannot be excluded. Since the two isoforms appear to have an opposite effect on tumour aggressiveness (Clinton et al, 1996;Qing et al, 1997;Roger et al, 1998;Twal et al, 2001;Du et al, 2002), the failure to discriminate the isoforms expressed in our series might have masked any impact on survival. The availability of isoform-specific reagents will enable analyses of potentially altered expression of the two isoforms.…”
Section: Discussionmentioning
confidence: 99%
“…Although coordinated expression of these two isoforms has been described , abnormal differential expression of the two isoforms in tumour tissues cannot be excluded. Since the two isoforms appear to have an opposite effect on tumour aggressiveness (Clinton et al, 1996;Qing et al, 1997;Roger et al, 1998;Twal et al, 2001;Du et al, 2002), the failure to discriminate the isoforms expressed in our series might have masked any impact on survival. The availability of isoform-specific reagents will enable analyses of potentially altered expression of the two isoforms.…”
Section: Discussionmentioning
confidence: 99%
“…Since there are four di erent alternatively spliced ®bulin-1 variants that may have distinct biological properties (Argraves et al, 1990;, we analysed the induction of ®bulin-1 variants and their relative expression in ovarian cancer cells. In this study, the induction of ®bulin-1 by estradiol ± previously described at the protein level (Galtier-Dereure et al, 1992;Clinton et al, 1996) ± is con®rmed at the mRNA level and is likely mediated through ERa. Moreover, we show that ®bulin-1C mRNA is more expressed than ®bulin-1D mRNA in ovarian cancer cells as compared to normal ovaries.…”
Section: Discussionmentioning
confidence: 99%
“…The ®bulin-1 protein is also present in the stroma of breast and ovarian tumors (Clinton et al, 1996;Roger et al, 1998). We have recently shown that ®bulin-1 protein expression is increased in human ovarian epithelial cancers as compared to normal and benign tumors and that epithelial ovarian cells expressed ®bulin-1 mRNA in vivo .…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…In keeping, we found that glycoprotein fibulin-1 (FBLN-1), a cysteine-rich, calcium-binding ECM and plasma molecule (Argraves et al, 1990), is aberrantly overtranscribed in epithelial tumor cell lines and breast surgical specimens, and that the protein is accumulated in the breast cancer-associated stroma, as detected immunohistochemically (Forti et al, 2002). Augmented expression of FBLN-1 has been also reported in human ovarian cancer cells stimulated with estrogens, and the resulting overexpression facilitated ovarian tumor cell invasion and progression (Clinton et al, 1996;Moll et al, 2002). FBLN-1 self-associates and binds to other ECM proteins, including fibronectin, laminin and nidogen, and to fibrinogen (Roark et al, 1995).…”
Section: Oncogenic Signals Of Ecm Componentsmentioning
confidence: 96%